Engineered NiO/TiO2 and CuO/NiO/TiO2 heterojunctions for sustainable direct photocatalytic epoxidation of propylene using molecular oxygen - Nicola Morante; Katia Monzillo; Alessandro Padua; Andrea Muscatello; Diana Sannino; Serena Esposito; Vincenzo Vaiano (Discover Nano)
Abstract The selective photocatalytic epoxidation of propylene using molecular oxygen under UV-A irradiation presents a promising sustainable alternative for propylene oxide (PO) production. In this study, NiO/TiO2 and CuO/NiO/TiO2 heterojunction photocatalysts were synthesized via the thermal annealing of sol-gel-derived TiO2 and tested in a fluidized bed photoreactor. Structural and optical characterizations confirmed the successful deposition of NiO onto TiO2 and highlighted the crucial role of NiO content in optimizing charge separation and catalytic efficiency. Among the NiO/TiO2 series, the NiO(1.1%)/TiO2 composite exhibited the lowest photoluminescence intensity, indicating reduced electron–hole recombination, while UV–Vis DRS analysis revealed a red shift in the absorption onset and a reduction in the band gap energy. These features resulted in enhanced light absorption and facilitated charge transfer, leading to superior photocatalytic performance compared to lower and higher NiO loadings. Under irradiation, NiO(1.1%)/TiO2 achieved a propylene conversion of 52.5%, a selectivity to PO of 83.4%, and a PO yield of 43.8%, confirming its effectiveness in promoting selective epoxidation. The introduction of CuO to form the CuO(1.1%)/NiO(1.1%)/TiO2 heterojunction further enhanced the catalytic performance, reaching 61% propylene conversion, 92% selectivity to PO, and a PO yield of 56%. The improved activity was attributed to the efficient conversion of molecular oxygen into hydrogen peroxide, which acts as a selective oxidant for epoxide formation. Process optimization revealed that water vapor (1000 ppm) significantly enhanced PO selectivity, while incident light intensity played a crucial role in determining conversion rates. The system exhibited excellent stability over 24 h of continuous operation, with no observable deactivation. Furthermore, an energy efficiency analysis demonstrated an exceptionally low energy consumption of 0.019 kWh per mole of propylene converted, significantly outperforming existing photocatalytic systems. These findings highlight the potential of CuO/NiO/TiO2-based photocatalysts, combined with fluidized bed reactors, as an energy-efficient and scalable approach for sustainable PO production.